A Plasmodium Cross-Stage Antigen Contributes to the Development of Experimental Cerebral Malaria - Fernandes, Priyanka; Howland, Shanshan W.; Heiss, Kirsten; Hoffmann, Angelika; Hernández-Castañeda, Maria A.; Obrová, Klára; Frank, Roland; Wiedemann, Philipp; Bendzus, Martin; Rénia, Laurent; Mueller, Ann-Kristin (Frontiers in Immunology, 2018)
Cerebral malaria is a complex neurological syndrome caused by an infection with Plasmodium falciparum parasites and is exclusively attributed to a series of host-parasite interactions at the pathological blood-stage of infection. In contrast, the preceding intra-hepatic phase of replication is generally considered clinically silent and thereby excluded from playing any role in the development of neurological symptoms. In this study however, we present an antigen PbmaLS_05 that is presented to the host immune system by both pre-erythrocytic and intra-erythrocytic stages and contributes to the development of cerebral malaria in mice. Although deletion of the endogenous PbmaLS_05 prevented the development of Experimental Cerebral Malaria (ECM) in susceptible mice after both sporozoite and infected red blood cell (iRBC) infections, we observed significant differences in contribution of the host immune response between both modes of inoculation. Moreover, PbmaLS_05-specific CD8+ T cells contributed to the development of ECM after sporozoite but not iRBC-infection, suggesting that pre-erythrocytic antigens like PbmaLS_05 can also contribute to the development of cerebral symptoms. Our data thus highlights the importance of the natural route of infection in the study of ECM, with potential implications for vaccine and therapeutic strategies against malaria.